Gas phase electronic structure of the 3d metal monoacetylides (MCCH, M = Sc .. Zn). Issue 2 (19th July 2016) - Dickerson, Shelby D.; DeYonker, Nathan J.
Abstract: The physical properties of gas phase metal monoacetylide (MCCH, where M = Sc–Zn) molecules have been evaluated with coupled cluster theory and multireference configuration interaction. Metal monoacetylides are isovalent to well‐studied metal monocyanides (MCN) and metal monoisocyanides (MNC), which suggests the MCCH series will have similar electronic structure. Some of the MCCH molecules, such as ScCCH, FeCCH, and CoCCH share a trait with their isoelectronic MCN/MNC counterparts: profound multireference character and low‐lying excited electronic states. Also like the MCN/MNC molecules, the MCCH species have rather large ligand dissociation energies. Due to the prevalence of C n H polyyne molecules discovered in the interstellar medium, members of the MCCH series likely exist as relevant astrochemicals and could be involved in prebiotic reactions. Abstract : The physical properties of gas phase metal monoacetylide (MCCH, where M = Sc–Zn) molecules have been evaluated with coupled cluster theory and multireference configuration interaction. Some of the MCCH molecules share a trait with their isoelectronic metal monocyanide counterparts: profound multireference character and low‐lying excited electronic states. Members of the MCCH series likely exist as relevant astrochemicals and could be involved in prebiotic reactions.